2011
DOI: 10.1007/s10067-011-1679-4
|View full text |Cite
|
Sign up to set email alerts
|

The presence of anti-citrullinated protein antibodies (ACPA) does not affect the clinical response to adalimumab in a group of RA patients with the tumor necrosis factor (TNF) α-308 G/G promoter polymorphism

Abstract: The introduction of antitumor necrosis factor (TNF) agents has improved the outcome for many patients with rheumatoid arthritis (RA). To date, the only replicated genetic predictor of anti-TNF response is the -308 G > A single-nucleotide polymorphism in the TNF promoter region. The presence of the -308 TNF G/G genotype appears to be a marker of good response to anti-TNF treatment. Anti-citrullinated protein antibodies (ACPA) have been linked with erosive disease, and have been established as the single most re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The lack of association between autoantibody status and radiographic progression in prednisolone-treated patients is consistent with similar findings in patients treated with some biological agents 11 12. It is further in line with the findings in the BEST study where the association of ACPA status with joint damage progression was significantly more pronounced in patients treated with initial methotrexate monotherapy compared with those getting combination therapy with prednisolone or anti-tumour necrosis factor agents 13.…”
Section: Discussionsupporting
confidence: 85%
“…The lack of association between autoantibody status and radiographic progression in prednisolone-treated patients is consistent with similar findings in patients treated with some biological agents 11 12. It is further in line with the findings in the BEST study where the association of ACPA status with joint damage progression was significantly more pronounced in patients treated with initial methotrexate monotherapy compared with those getting combination therapy with prednisolone or anti-tumour necrosis factor agents 13.…”
Section: Discussionsupporting
confidence: 85%
“…Previous single studies have suggested that the presence of RF and anti-CCP antibody is associated with a reduced response to anti-TNFα treatment [7]–[14];_ENREF_9 however, a number of studies have reported a contrasting conclusion [15]–[19]. Thus, to investigate whether the status of RF or anti-CCP antibody in RA patients has predictive value for a clinical response to anti-TNFα treatment, we performed a meta-analysis by a comprehensive literature search and inclusion of all of the available qualifying studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that the status of RF or anti-CCP antibody in RA patients is associated with a clinical response to anti-TNFα treatment [7]–[14], whereas such a correlation was not found in other studies [15]–[19]. Thus, no definite conclusion has been reached to date.…”
Section: Introductionmentioning
confidence: 96%
“…The -857 C/T single nucleotide polymorphisms (SNP) in the TNFA (TNF-a) promoter region was associated with significantly increased response to etanercept treatment in RA patients [Kang et al, 2005]. Also, the -308 G4A SNP in the TNFA promoter predicts response to anti-TNF-a therapies in patients with RA or spondyloarthritis [Seitz et al, 2007;Soto et al, 2011]. Advances in molecular research may help elucidate the multifaceted roles of TNF-a in cutaneous pathology and open the way for an individualized treatment approach.…”
Section: Discussionmentioning
confidence: 99%